2001
DOI: 10.1164/ajrccm.163.5.9903053
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Long-acting Inhaled β2-Adrenergic Agonist, Salmeterol Xinafoate, in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a condition in which continuous bronchodilation may have clinical advantages. This study evaluated salmeterol, a beta-agonist bronchodilator with a duration of action substantially longer than that of short-acting beta-agonists, compared with ipratropium, an anticholinergic bronchodilator, and placebo in patients with COPD. Four hundred and five patients with COPD received either salmeterol 42 microg twice daily, ipratropium bromide 36 microg four times daily, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
148
0
13

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(171 citation statements)
references
References 21 publications
10
148
0
13
Order By: Relevance
“…1,2 Nonetheless, it has been shown that the use of spirometry is limited with only a third of newly diagnosed individuals with COPD actually having spirometry to confirm the presence of irreversible air flow obstruction. [3][4][5] Although appropriate therapy with inhaled medications have been demonstrated to reduce symptoms, improve health-related quality of life, and decrease the rate of acute exacerbations [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , there is growing evidence that pharmacotherapy used to treat patients for COPD pose risks. 6,7,[20][21][22][23][24][25] Without spirometry, patients who have been diagnosed with COPD may be being medically managed without evidence of airways obstruction, leading to unnecessary exposure to risks and costs associated with COPD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nonetheless, it has been shown that the use of spirometry is limited with only a third of newly diagnosed individuals with COPD actually having spirometry to confirm the presence of irreversible air flow obstruction. [3][4][5] Although appropriate therapy with inhaled medications have been demonstrated to reduce symptoms, improve health-related quality of life, and decrease the rate of acute exacerbations [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , there is growing evidence that pharmacotherapy used to treat patients for COPD pose risks. 6,7,[20][21][22][23][24][25] Without spirometry, patients who have been diagnosed with COPD may be being medically managed without evidence of airways obstruction, leading to unnecessary exposure to risks and costs associated with COPD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the hypothetical patients were selected to closely reflect the characteristics of the patient population included in the randomized clinical trials of the treatments. 15,18,19,22 Cycle length…”
Section: Model Characteristics Patient Populationmentioning
confidence: 99%
“…The efficacy data for the no treatment group are the data obtained for placebo arms of clinical trials for tiotropium and salmeterol. 15,18,19,22 For tiotropium, 3 studies were identified. In a study by Casaburi and colleagues,18 the exacerbation rate per patient per year for tiotropium was 0.086.…”
Section: Operationalizing the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the very varied quality of community prevalence data have to be relied upon to draw these conclusions, the use of randomised controlled trials to evaluate the efficacy of treatment for COPD is more reliable. This approach has now yielded a large body of scientific data, which confirm that long-acting b-agonists (LABA) improve lung function and health status in stable COPD [3][4][5] whilst also increasing the time between exacerbations [4,6]. Likewise, largescale 3-yr randomised studies have failed to find any effect of inhaled corticosteroids on the rate of decline of the forced expiratory volume in one second (FEV1), but in more severe patients, these drugs reduce the number of exacerbations [7][8][9][10].…”
mentioning
confidence: 99%